1990
DOI: 10.1002/ajmg.1320360408
|View full text |Cite
|
Sign up to set email alerts
|

Fanconi anemia in black African children

Abstract: Fanconi anemia (FA) has rarely been reported in black children either in the United States or Africa. This report describes 25 black African children with FA seen in Johannesburg over an 11-year period. The prevalence of homozygotes was estimated to be 1:476,000. Clinical manifestations, mean age at diagnosis, and hematologic and chromosome abnormalities were similar to those described in other ethnic groups. Response to androgens was poor and most patients required regular transfusions. Seventeen (68%) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
(3 reference statements)
2
11
2
Order By: Relevance
“…The true incidence of FA would be higher, since this mutation accounts for 80% of FA alleles in the population and is therefore likely to be about 10-fold higher than that reported from clinical ascertainment of FA in black school children and estimates of population size from a population census. 5 We also investigated the clinical phenotype of black South African patients homozygous for the FANCG deletion. Detailed clinical information was available from 20 patients, and this was compared to data from 20 European FA-G patients and from all 245 European FA patients described previously.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The true incidence of FA would be higher, since this mutation accounts for 80% of FA alleles in the population and is therefore likely to be about 10-fold higher than that reported from clinical ascertainment of FA in black school children and estimates of population size from a population census. 5 We also investigated the clinical phenotype of black South African patients homozygous for the FANCG deletion. Detailed clinical information was available from 20 patients, and this was compared to data from 20 European FA-G patients and from all 245 European FA patients described previously.…”
Section: Resultsmentioning
confidence: 99%
“…4 Clinical studies indicated that FA is rare in black South Africans, with a homozygote prevalence of 1 in 476 000. 5 We investigated the molecular basis of FA in this population to inform future patient management strategies.…”
Section: Fancc Fancd1/brca2 Fancd2 Fance Fancf Fancg Fanci Fanmentioning
confidence: 99%
“…9 Notwithstanding advances in standards of care, the health-care system in South Africa remains underdeveloped and is largely based on semi-urban and rural primary health-care clinics that are predominantly staffed by nurses. Despite the severity of FA, it has previously been postulated that only a small percentage of affected patients are recognized in these local and regional health-care institutions and referred for tertiary management 9,10 although the reasons for this remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Evidence further suggested that the clinical manifestations of FA in this population were similar to those in other ethnic groups. [12] This finding was further confirmed in a comparative study of FA in various SA ethnic groups. [13] Newer studies in black patients with known FANCG mutations have identified both similarities and differences with regards to the phenotypic manifestations of FA.…”
mentioning
confidence: 62%
“…Initial reports seemed to suggest FA in black individuals was very rare. [12] However, Macdougall et al [13] estimated the incidence of FA in this population as 1/476 000 in a case-based ascertainment study. More recently, gene frequency studies have shown that FA has a carrier frequency of 1/100 in black SA patients and therefore an expected birth incidence of 1/40 000.…”
mentioning
confidence: 88%